Penerapan Prinsip Manajemen Syariah dalam Usaha Mikro: Studi Kasus di Kecamatan Gunung Tanjung, Kabupaten Tasikmalaya - Farida Yanti, Reni (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
Micro-enterprises play a strategic role in Indonesia's economy, particularly in rural areas, yet face challenges in implementing management principles aligned with the religious values of society. In the context of a Muslim-majority society, the integration of Islamic values through sharia management has become increasingly relevant, although its implementation at the micro-enterprise level remains sub-optimal. This study explores the implementation of Islamic management principles in micro-enterprises within Gunung Tanjung District, Tasikmalaya Regency. Using a qualitative case study approach, data were collected through in-depth interviews with eight micro-entrepreneurs, participatory observation, and documentation analysis over six months (January-June 2024). The research analyzed the implementation of five core principles: tauhid, amanah, adl, shura, and ihsan. Findings reveal diverse implementation patterns with three practitioner categories: Intuitive Implementers (62.5%), Conscious Adopters (25%), and Aspiring Learners (12.5%). While micro-entrepreneurs intuitively apply Islamic values, systematic implementation remains limited. Key challenges include limited managerial literacy (87.5% of respondents), inadequate institutional support, and lack of structured training programs. The research demonstrates that Islamic management principles can enhance business sustainability, customer trust, and community engagement. The study recommends developing practical Islamic management guidelines for micro-enterprises and establishing collaborative support systems that involve local government, Islamic financial institutions, and religious organizations.